De Kalmthoutse of Grijze school : en haar tijdgenoten - Van Aert, Marina; Bastiaensen, Jean (Tielt : Lannoo, 2007)
Lamorinière, François ; Huberti, Edourd ; Plumot, André ; Verheyden, Isidore ; Verstraete, Theodoor ; Van Leemputten, Frans ; Van Kuyck, Frans ; Courtens, Franz ; Rul, Henry ; De Vadder, Franz ; Van De Velde, Henry ; Delderenne, Leon ; Larock, Evert
boek
Keywords: Rosseels, Jacques; Meyers, Isodore; Heymans, Adrien Joseph; Crabeels, Florent; Baron, Théodore